Critical religion and critical research on religion: A response to the April 2016 editorial. (December 2016) - Fitzgerald, Timothy
This response takes up some of the editorial comments for further clarification and critique. My point has been that 'politics' is as much a modern invention as 'religion'. We cannot understand the rhetorical function of 'religion' if we treat it as a stand-alone category referring to some supposed object or objects in the world. I am especially concerned here to keep in view the oscillating binary categories of which 'religion' forms one parasitic half, and 'politics' or 'science' the other. This critical problematization of the liberal categories of the understanding opposes and challenges their current institutionalization in the liberal academy, where they now serve the Neoliberal agenda and the reproduction of the dominant, globalising imperatives of private property.